Weighted Approximation of Functions by Meyer–König and Zeller Operators of Max-Product Type. (26th April 2018) - Holhoş, Adrian
ABSTRACT: In this paper, we study the uniform approximation of functions by Meyer–König and Zeller operators of max-product type in some weighted spaces. We estimate the rate of approximation in terms of a suitable modulus of continuity.